PEMIKIRAN IKHWANUS SHAFA TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN ERA GLOBALISASI - Anwar, Khaerul (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
The world of education, especially in Indonesia, is still faced with various problems. This situation is very visible, began to shift the educational orientation of the students who tend to make education only as a "road of formality" to get work in the future, to the problems of curriculum, learning methods, teachers, and others. This is inseparable from the era of globalization and modernization that is developing rapidly. In solving this problem, it is necessary to present philosophical ideas, among which are the thoughts of the Ikhwanus Shafa. This research is included in library research (Library Research). The sources of research data include primary data and secondary data. Ikhwanus Shafa is a secret society engaged in science. This group adheres to a religious-rational school. The thought of Ikwanus Shafa, who holds that educational goals must be related to religious values, has been implemented at Sunan Kalijaga State Islamic University in Yogyakarta with the concepts of integration and interconnection. In addition, the Ikhwanus Shafa's educational methods inspire many educators by teaching from the concrete to the abstract by providing contextual examples with everyday life. In terms of the characteristics that must be possessed by students and teachers, can be found in Islamic boarding schools by accustoming the traits of exemplary and exemplary in everyday life.